Hubungan Memahami Kosakata dengan Menulis Teks Pidato Siswa SMA Plus Muhammadiyah Natar - Rangga Yudha; Iqbal Hilal; Edi Suyanto (FKIP Universitas Lampung, 2019)
Based on the results of the research conducted, the average value of class X (variable x) is 79.00 (good) and the average (variable y) is 82.00 (good). Eleventh grade students (variable x) is 81.00 (good) and average (variable x) is 83.00 (good). Twelvth grade students (variable x) is 83.00, (good) and the average value (variable x) is 83.00 with (good). The results of the hypothesis test proposed